2020
DOI: 10.1108/meq-01-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Corporate environmental performance–financial performance relationship in India using eco-efficiency metrics

Abstract: PurposeThe purpose of this study is to attempt to empirically examine the impact of disaggregate, eco-efficiency-based measures of corporate environmental performance (CEP) on corporate financial performance (CFP) of Indian companies. Further, recent theories contending a bidirectional causality between them is also explored.Design/methodology/approachSecondary data of 224 Indian S&P 500 companies from 2002 to 2011 are used to run panel data regression models for examining the impact of CEP measures on acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…Analytically, despite multiple authors supporting a negative or neutral link between EP and FP (Santis et al, 2016;Lucato et al, 2017), many studies have found a positive relationship between firm's EP and FP (Nishitani, 2011;Bergmann et al, 2017;Gómez-Bezares et al, 2017;Manrique and Martí-Ballester, 2017;Gangi et al, 2020;Liu, 2020;Sudha, 2020). Similarly, multiple literature surveys and meta-analysis papers have come to the same conclusion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analytically, despite multiple authors supporting a negative or neutral link between EP and FP (Santis et al, 2016;Lucato et al, 2017), many studies have found a positive relationship between firm's EP and FP (Nishitani, 2011;Bergmann et al, 2017;Gómez-Bezares et al, 2017;Manrique and Martí-Ballester, 2017;Gangi et al, 2020;Liu, 2020;Sudha, 2020). Similarly, multiple literature surveys and meta-analysis papers have come to the same conclusion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These countries are characterized by the absence of clear regulations, underdeveloped capital markets and inadequate data on emissions (Dasgupta et al, 2001;Dasgupta et al, 2006;Pargal & Wheeler, 1996;Sarkar & Sarkar, 2012). Furthermore, only a handful of studies have been conducted in Indian context (Gupta & Goldar, 2005;Kumar & Shetty, 2017;Shashi et al, 2019;Singh et al, 2020;Sudha, 2020). Despite regulatory measures in place, ground reality in India is disheartening with weak implementation of existing regulations, non-availability of environmental performance data, poor follow-up of previous regulatory actions and widespread bureaucracy and corruption (Kumar & Managi, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Services might have low environmental impact at point of generation but the direct and indirect environmental effects of their supply chain in form of energy usage, carbon emissions and waste generation merit further investigation (Gil et al, 2001;Rosenblum et al, 2000). In the Indian context, existing studies measuring the impact of environmental practices on firm performance (Gupta and Goldar, 2005;Kumar & Shetty, 2017;Shashi et al, 2019;Singh et al, 2020;Sudha, 2020) have focused on manufacturing sector while India is predominantly a service driven economy; the service sector accounts for 55.39% share in country's Gross Value Added (Ministry of Finance, 2020). 1 Given the energy intensity and economic importance of service sector, it will be worth examining the relationship between the EMPs adopted by the firms in this sector and their financial performance.…”
Section: Introductionmentioning
confidence: 99%
“…Using green teams of employees as an indicator of environmental management capability, Dangelico (2015) showed that such green teams positively affect the environmental performance and environmental reputation. In another study by Sudha (2020), positive bidirectional causality was found between CEP and CFP, while using a different measure to capture environmental performance, that is, eco‐efficiency‐based CEP metrics in Indian context. Also, Yagi and Managi (2018) supported the positive association between CEP and CFP and performed a decomposition analysis of environmental performance in terms of carbon dioxide (CO 2 ) and greenhouse gas emissions.…”
Section: Evolution Of Research Themes Using Couplingmentioning
confidence: 99%